2019
DOI: 10.1016/j.corsci.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical noise measurements on stainless steel using a gelled electrolyte

Abstract: The present paper presents pioneering results about the use of the electrochemical noise (EN) technique to study corrosion of metal surfaces of complex geometry in a gel electrolyte based on agar-glycerol, the composition of which was previously optimized for electrochemical measurements on stainless steel (SS) surfaces. EN results obtained with AISI 304 SS electrodes in both gelled and liquid electrolytes using three different modes (zero-resistance ammeter, potentiostatic, galvanostatic) of measurements have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…3). The zero resistance ammeter (ZRA) mode was adopted for detection, and the sampling frequency was 2 Hz [6,20]. The DC components in all the EN data were removed using a quintic polynomial fitting [21][22][23].…”
Section: En Measurement System and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The zero resistance ammeter (ZRA) mode was adopted for detection, and the sampling frequency was 2 Hz [6,20]. The DC components in all the EN data were removed using a quintic polynomial fitting [21][22][23].…”
Section: En Measurement System and Experimentsmentioning
confidence: 99%
“…The electrochemical noise (EN) technique has been widely used in atmospheric corrosion detection because its detection equipment is simple and portable and can be used for remote continuous monitoring [3]. The application of EN technique requires proper data analysis [4][5][6], and the establishment of a reliable electrode system in the atmospheric environment [7,8]. The data analysis of EN can represent the characteristic parameters of the corrosion type and corrosion degree of metal materials through time domain analysis, frequency domain analysis, and time-frequency analysis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible replacement for the standard setup are gel electrolytes. Several studies on bare and coated bronzes have been conducted with gel based on agar [ 21 , 22 , 23 , 24 ] containing artificial rain solution. It has been shown that in such medium good electrochemical response is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Moreover, a significant amount of information considering the localized corrosion is provided by this technique as compared with the traditional ones. [22][23][24][25][26][27] There are a limited number of instances of employment of EN analytic method for magnesium alloys. [28] EN assessments are commonly performed using two working electrodes (WEs) whose connection is provided through a zero-resistance ammeter (ZRA), which monitors the coupling current of inter-WEs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13–21 ] Moreover, a significant amount of information considering the localized corrosion is provided by this technique as compared with the traditional ones. [ 22–27 ] There are a limited number of instances of employment of EN analytic method for magnesium alloys. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%